Finite‐time disturbance observer based integral sliding mode control for attitude stabilisation under actuator failure. Issue 1 (1st January 2019) - Li, Bo; Hu, Qinglei; Yang, Yongsheng; Postolache, Octavian Adrian
Abstract : This work develops a novel disturbance observer and integral sliding mode technique based fault tolerant attitude control scheme for spacecraft, which is subject to external disturbance torques and actuator failures. More specifically, a simple and novel finite‐time disturbance observer is first designed to reconstruct the synthetic uncertainty deriving from actuator failures and disturbances, by which the synthetic uncertainty is also compensated or restricted. Then, an integral sliding mode based finite‐time fault tolerant attitude stabilisation controller incorporating with an adjusting law is investigated to ensure the closed‐loop attitude control system converge to the stable region in finite time. And also the finite‐time stability of the closed‐loop attitude control system driven by the proposed attitude control scheme is analysed and proved utilising Lyapunov methodology. Finally, a simulation example for a rigid spacecraft model is carried out to verify the effectiveness and superiority of the proposed attitude control approach.